The Influence of Workload and Burnout on Turnover Intention among SPPG Officers: The Mediating Role of Job Stress in Anyer District, Serang Regency - Muhammad Rahman Afifi; Gema Ika Sari; Udin Suadma (Economics and Digital Business Review, 2026)
The high operational demands of the Free Nutritional Meal Program (MBG) which have the potential to increase workload, burnout, work stress, and employees' desire to leave the organization are the background to this study. This study aims to analyse the influence of workload and burnout on turnover intention through work stress as a mediating variable on Nutrition Fulfilment Service Unit officers in Anyer District, Serang Regency. This study employed a quantitative approach with a survey method. The study population comprised all SPPG officers in Anyer District, with a sample size of 202 respondents determined using proportionate random sampling. Data collection was conducted through a questionnaire that met validity and reliability tests. Data analysis used Structural Equation Modelling based on Partial Least Squares (SEM-PLS) to examine the direct and indirect effects between variables. The results showed that workload had a positive and significant effect on turnover intention (β = 0.197; t = 2.461; p = 0.014) and job stress (β = 0.356; t = 4.787; p < 0.001). Burnout also had a positive and significant effect on turnover intention (β = 0.296; t = 3.768; p < 0.001) and job stress (β = 0.581; t = 9.047; p < 0.001). Furthermore, job stress had a positive and significant effect on turnover intention (β = 0.434; t = 5.361; p < 0.001). The indirect effect test showed that job stress significantly mediated the effect of workload on turnover intention (β = 0.154; t = 3.886; p < 0.001) and mediated the effect of burnout on turnover intention (β = 0.252; t = 4.384; p < 0.001). Thus, all research hypotheses were accepted. This study concludes that increased workload and burnout, both directly and through work stress, can increase the turnover intention of SPPG officers. Burnout is the factor that has the greatest influence on work stress (β = 0.581), while work stress is proven to be a mediating mechanism that strengthens the influence of workload and burnout on turnover intention. These findings imply that workload management, burnout prevention, and work stress control need to be a priority in human resource management strategies at SPPG to retain employees, improve work welfare, and ensure the sustainability of the Free Nutritional Meal Program.